Optimization of bacterial polyhydroxyalkanoate production by using one-factor-at-a-time approach - ASEEM WAGLE; YOGINI DIXIT; BABU VAKIL (International Journal of Pharma and Bio Sciences, 2017)
Polyhydroxyalkanoates(PHA), an ecofriendly alternative to synthetic plastics are synthesized by bacteria under unfavorable growth conditions. Its production can be controlled to a large extent by optimizing various influencing factors like type of microorganism, nutrient availability, environmental conditions of growth, etc. The present study was aimed to maximize PHA production by selected bacteria using one-factor-at-a-time approach(OFAT) using shake flask fermentation process. Six previously isolated bacterial cultures were identified by 16 S rRNA sequencing. Two bacteria identified as Brucella melitensis and Microbacterium aurum were found to be novel PHA producers. All isolates were optimized for physical and nutritional parameters which led to significant increase of 25-40% in the PHA yield as measured by gravimetric analysis. Three isolates namely Bacillus flexus, Brucella melitensis and Pseudomonas aeruginosa giving maximum PHA yield of 43.04 ±1.09, 47.38 ±1.31 and 49.06 ±0.75 % respectively after optimization and were found to be potential candidates for further optimization.